AN ANALYSIS OF TEACHER'S LOCUTIONARY SPEECH ACTS IN LEARNING ENGLISH AT SMAN 3 BULUKUMBA - pratama, Andi dinasti indra; Muhammad Asrianto Setiadi; Ardiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study investigates the use of locutionary speech acts by English language teacher’s during classroom instruction at SMAN 3 Bulukumba. Language in education plays a crucial role not only as a tool for delivering instructional content but also as a medium for fostering interaction, building relationships, and managing the classroom environment. Grounded in Austin’s Speech Act Theory, this research specifically focuses on two components of locutionary acts: phatic acts and rhetic acts. Phatic acts are examined in terms of their interpersonal functions, such as initiating greetings, checking student well-being, expressing appreciation, and fostering classroom rapport. Rhetic acts, on the other hand, are explored for their instructional value in delivering content, stating facts, providing directions, expressing opinions, and persuading students to participate and engage with the lesson material. This research employs a qualitative descriptive methodology, with data collected through systematic classroom observations two English teacher’s at the senior high school level. The utterances collected were analyzed using a framework informed by Austin's typology of speech acts, focusing on how teacher’s structure their discourse to achieve pedagogical goals. The findings demonstrate that both phatic and rhetic acts are consistently utilized across different stages of instruction, serving both social and academic functions in the classroom. Phatic acts were particularly evident in teacher-student interactions at the beginning and end of lessons, helping to establish a warm and welcoming classroom climate. Meanwhile, rhetic acts were predominantly used during lesson delivery and student engagement, emphasizing clarity, structure, and motivational discourse. Classroom transcripts and observation tables provide empirical evidence of how these speech acts function in practice, revealing that their strategic use not only facilitates communication but also enhances student motivation, comprehension, and classroom dynamics. The study concludes that locutionary speech acts are integral to effective teaching and recommends their intentional application as part of teacher communication strategies. These findings have implications for teacher training programs, highlighting the need to develop pragmatic awareness among educators, particularly in EFL contexts where language functions extend beyond semantics to include social interaction and cultural sensitivity. Keywords: locutionary, phonetic act, phatic act, rhetic act, teacher